(untitled) (Environment & Health, 2023)
Aim: to define the criteria of estimation of harmful action of industrial wastes by the different ways of entering organism. Objects and research methods. The objects of the study were industrial waste from various branches of enterprises. Research methods: sanitary-chemical, toxicological, radiological, biological: according to bacteriological and helminthological indicators, the method of hygienic analysis. Results of research and their discussion. The study of industrial waste from various branches of origin made it possible to establish that the physico-mechanical and chemical properties of waste determine the effects of their action on the body and are one of the important criteria for harmful effects on the health of the population. Red sludge - waste in the form of a powdery mass of finely dispersed particles), highly volatile, has a high ability to form dust. The content of toxic compounds of heavy metals in the form of hydroxides (pH - 11.7) characterizes the waste as dangerous when entering the body by inhalation, oral and percutaneous means. Thermal energy waste - fly ash, ash-slag mixtures, slurries containing toxic compounds of metals, mainly vanadium, differ in physical and mechanical properties and chemical composition, which determines their dangerous properties. When inhaled into the body, such waste belongs to class II - highly dangerous substances. Waste from the tailings depository of the Ingulets Mining and Processing Plant is characterized by a high content of toxic iron compounds (Fe - 14.5%) and a dust factor, which is the most dangerous for atmospheric air pollution with a harmful effect on human respiratory organs. For waste of organic origin, the most important evaluation criterion is biological (microbiological and helminthological) indicators, which guarantee the degree of epidemiological safety of such waste. The results of our research allow us to state that industrial waste from the most common industries is characterized by hazardous properties, the predominant factor of which is the dust factor, which must be taken into account when handling such waste, and the introduction of modern dust suppression technologies. It is also necessary to take into account that in the waste composition of even one branch of industry, chemical compounds are characterized by various negative effects on the body. Therefore, a comprehensive sanitary-epidemiological assessment of waste with the determination of its dangerous properties according to medical criteria, establishing the hazard class of waste in various ways of entering the body is the basis for preventing their negative impact on the health of the population, which will contribute to the development of measures for controlled waste management. Conclusions. Taking into account the hazardous properties of waste according to medical criteria is an important factor necessary for conducting a comprehensive sanitary-epidemiological assessment of industrial waste and developing measures for controlled waste management.